Carta do rei de Portugal e príncipe de Castela D. Manuel a Diogo Lopes de Lima (1498) - Reis, Pedro (2022)
1498, Lisboa, janeiro, 4 Carta do rei de Portugal e príncipe de Castela D. Manuel a convocar Diogo de Lopes de Lima assim que recebesse a dita carta. 4 January 1498, Lisbon Letter from the King of Portugal and Prince of Castile, Dom Manuel, summoning Diogo de Lopes de Lima as soon as he received the aforementioned letter.